2008
DOI: 10.1002/cncr.23787
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization or chemoinfusion for unresectable intrahepatic cholangiocarcinoma

Abstract: BACKGROUND.The role of transcatheter arterial chemoembolization (TACE) or transcatheter arterial chemoinfusion (TACI) for unresectable intrahepatic cholangiocarcinoma (ICC) has recently been questioned. The aim of the study was to evaluate the clinical efficacy of TACE or TACI in patients with unresectable ICC and to identify prognostic factors associated with clinical success.METHODS.From 1997 to 2007, 49 patients with unresectable ICC were treated with TACE (n = 124) or transcatheter arterial chemoinfusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 36 publications
1
50
0
5
Order By: Relevance
“…The study of Kim et al 48 showed that hypovascular tumor, Child-Pugh class B and large tumor size were poor prognostic factors for patient's survival, there the median and mean survival times were 10 and 18 months after TACE or chemoinfusion with Cisplatin. The survival rates were 52% at 1 year, 38% at 2 years and 16% at 3 years.…”
Section: Cancer Therapymentioning
confidence: 99%
“…The study of Kim et al 48 showed that hypovascular tumor, Child-Pugh class B and large tumor size were poor prognostic factors for patient's survival, there the median and mean survival times were 10 and 18 months after TACE or chemoinfusion with Cisplatin. The survival rates were 52% at 1 year, 38% at 2 years and 16% at 3 years.…”
Section: Cancer Therapymentioning
confidence: 99%
“…First, details regarding tumor vascularity on angiography in all patients were not provided. In our previous report [2], the tumor blush was not identified on angiography in 26% (13/49) of the patients with intrahepatic cholangiocarcinoma. Trancatheter arterial chemoinfusion was performed for these patients because it is not easy to decide whether to perform embolization of the right or left hepatic artery or the segmental artery despite the possible embolization-related complications.…”
Section: To the Editormentioning
confidence: 72%
“…Generally, tumor size and reserved liver functions are important factors for survival period in patients who undergo palliative therapy for hepatic malignancy [2,3]. Therefore, significant selection bias might not have been eliminated in their study.…”
Section: To the Editormentioning
confidence: 99%
“…Target methods, aiming to direct the treatment locally inside the tumor, are valid alternatives to systemic chemotherapy for unresectable CCA, including thermal ablation with radiofrequency ablation or microwave ablation, and chemoembolization (21)(22)(23). Figure …”
Section: Discussionmentioning
confidence: 99%
“…TACE can be performed using several drugs, such as gemcitabine, mitomycin C and doxorubicin (23,24).…”
Section: Effects Of Transarterial Chemoembolization (Tace) On Intramentioning
confidence: 99%